Combined Adenosquamous and Large Cell Neuroendocrine Carcinoma of the Gallbladder - Jiyoon Jung; Yang-Seok Chae; Chul Hwan Kim; Youngseok Lee; Jeong Hyeon Lee; Dong-Sik Kim; Young-Dong Yu; Joo Young Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Large cell neuroendocrine carcinoma (LCNEC) of the gallbladder is extremely rare and usually combined with other type of malignancy, mostly adenocarcinoma. We report an unusual case of combined adenosquamous carcinoma and LCNEC of the gallbladder in a 54-year-old woman. A radical cholecystectomy specimen revealed a 4.3×4.0 cm polypoid mass in the fundus with infiltration of adjacent liver parenchyma. Microscopically, the tumor consisted of two distinct components. Adenosquamous carcinoma was predominant and abrupt transition from adenocarcinoma to squamous cell carcinoma was observed. LCNEC showed round cells with large, vesicular nuclei, abundant mitotic figures, and occasional pseudorosette formation. The patient received adjuvant chemotherapy. However, multiple liver metastases were identified at 3-month follow-up. Metastatic nodules were composed of LCNEC and squamous cell carcinoma components. Detecting LCNEC component is important in gallbladder cancer, because the tumor may require a different chemotherapy regimen and show early metastasis and poor prognosis.